Ethylene and 1-mcp affect the postharvest behavior of yellow pitahaya fruits (selenicereus megalanthus haw.) (2014)
The pitahaya or dragon fruit is one of the most representative exotic fruits that Colombia has, with an important, growing international market, but the cultivation and postharvest of this fruit lack sufficient technological support to be more competitive. Therefore, alternatives that provide good-quality products that meet market requirements are very important. Therefore, the objective of this research was to determine the effect of a ripening retardant and ethylene application on the conservation and quality of pitahaya fruits and the possible changes during ripening associated with ethylene, for which a completely randomized design with three treatments was used, corresponding to the application of ethylene (ethephon, 3 mL L-1), 1-methylcyclopropene (1-MCP, 600 mg L-1) and a control, with four replications, for a total of 12 experimental units. The fruits were stored at 18°C with 75% relative humidity. The 1-MCP application significantly decreased the loss of firmness, total soluble solids, loss of fresh mass and respiratory rate. Fruits from the control and ethylene treatment tended toward a climateric respiratory behavior. The total carotenoid content of the fruits was significantly higher in the ethylene application and the control treatment, which was consistent with the color change of the fruits. It can be concluded that the 1-MCP application reduced the ethylene action, slowing the ripening of the dragon fruits.